Production of passion fruit seedlings by grafting using native passiflora species rootstocks (Research, Society and Development, 2020)
To obtain uniform passion fruit plantations, the aim of this research is to analyze the development of rootstocks and grafted seedlings, using the following treatments: non-grafted Passifora edulis and grafted with two different method: single grafting, P. edulis on P. caerulea and P. edulis on P. giberti, and double grafting, P. edulis on P. giberti and P. caerulea, on the same plant, with 3 replicates in 2 blocks. The germinative potential of seeds of the three species used was evaluated according to the storage period, viability of the grafting methods used, plant height after the juvenile period and relative growth rate. It was observed that treatments of passion fruit on P. caerulea obtained good initial development, reducing more sharply in the last data collection compared to treatments of passion fruit on P. giberti and double grafting. For non-grafted passion fruit, there was matter accumulation at the beginning of plant development, with reduction throughout collections, with tendency to stabilization, mainly approaching flowering. It was verified that non-grafted plants tend to start developing first, showing physiological advance, when compared to double grafting or single grafting with P. caerulea, also due to the rootstock vigor, which presents low potential. Using P. giberti as a rootstock seems to be more viable for the passion fruit culture.